'Keep Them on the Straight and Narrow': Understanding, Selecting and Governing Subjects Through Intensive Supervision Units. (7th December 2020) - Lecoq, Garrett; Ballucci, Dale; Spencer, Dale
Abstract: Drawing from focus groups and semi-structured interviews, this paper examines decision-making practices and monitoring techniques of Canadian Intensive Supervision Units (ISUs) managing high-risk individuals in the community. We argue that ISU subjects are hyper-individualized through their unique conditions of release, contesting notions that actuarial risk assessments have eclipsed individual understandings of dangerousness in risk, correctional and policing literature. Using Foucault's disciplinary, pastoral and confessional dispositifs, we highlight how ISU agents make subjects active participants in their own punishment. Moreover, we illustrate how dispositifs not only allow ISU agents to understand, select and govern subjects but also, more problematically, transform subjects into ostensibly dangerous entities reifying and necessitating escalating criminal justice interventions under auspices of protecting the community from potential—not guaranteed—harm.